The Influence of Game Series and Fundamental Motor Skills (FMS) Learning Strategies on Volleyball Technique Skills of Elementary School Students 006 Madung - Afeldi Yelmon Zirman; Syahrial Bakhtiar; Wilda Welis; Alnedral Alnedral (STKIP Singkawang, 2025)
This study investigates the impact of game-based learning strategies versus conventional approaches on developing elementary school students' basic volleyball skills. Using an experimental design, two groups received different treatments: game-based learning and conventional methods. The sample consisted of 60 fifth-grade students, assessed for fundamental motor skills using the TGMD-2 subtest and basic volleyball techniques using the AHHPERD instrument designed for ages 10-18. Data analysis using descriptive statistics and a 2x2 ANOVA yielded the following findings: (1) Game-based learning strategies were more effective than conventional approaches in improving basic volleyball technique skills (p = 0.030), (2) Students with high fundamental motor skills (FMS) showed significantly better basic volleyball technique skills compared to those with low FMS (p = 0.039), (3) There was a significant interaction between learning strategies and students' FMS (p = 0.013), indicating varying effectiveness based on FMS levels, (4) Game-based learning strategies were more effective in enhancing basic volleyball technique skills in students with high FMS compared to conventional methods (p = 0.003), (5) Conventional learning strategies were more effective than game-based approaches in improving basic volleyball skills in students with low FMS (p = 0.011.